2020
DOI: 10.1111/pce.13968
|View full text |Cite
|
Sign up to set email alerts
|

Dividing the pie: A quantitative review on plant density responses

Abstract: Plant population density is an important variable in agronomy and forestry and offers an experimental way to better understand plant-plant competition. We made a meta-analysis of responses of even-aged mono-specific stands to population density by quantifying for 3 stand and 33 individual plant variables in 334 experiments how much both plant biomass and phenotypic traits change with a doubling in density. Increasing density increases standing crop per area, but decreases the mean size of its individuals, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 265 publications
(124 reference statements)
8
71
1
Order By: Relevance
“…In our study, plants growing at high densities allocated more biomass to roots, indicating that competition was more intense for below-ground resources than for light, even at high nutrient levels. In contrast, a recent meta-analysis found that at high densities most plants allocate more biomass to stems, and concluded that higher density predominantly increases competition for light (Postma et al 2020).…”
Section: Effects Of Nutrients and Density On Biomass Allocationmentioning
confidence: 81%
See 4 more Smart Citations
“…In our study, plants growing at high densities allocated more biomass to roots, indicating that competition was more intense for below-ground resources than for light, even at high nutrient levels. In contrast, a recent meta-analysis found that at high densities most plants allocate more biomass to stems, and concluded that higher density predominantly increases competition for light (Postma et al 2020).…”
Section: Effects Of Nutrients and Density On Biomass Allocationmentioning
confidence: 81%
“…However, plants can also respond to different environments by changing morphological or physiological traits , Freschet et al 2015, Kramer-Walter & Laughlin 2017, Sandner & Matthies 2018, Poorter et al 2019). For example, in response to shade by competitors, plants may increase their specific stem length (Poorter et al 2019, Postma et al 2020 and in response to nutrient shortage due to competition may increase their specific root length (Schippers & Olff 2000, Trubat et al 2006, Dybzinsky et al 2019, but see Freschet et al 2015, Kramer-Walter et al 2017).…”
Section: Accepted Articlementioning
confidence: 99%
See 3 more Smart Citations